An Essay in Praise of Scholastic Theology - Holmes, Austin (Lumen et Vita, 2018)
This essay attempts to give the Scholastic Theology of the High Middle Ages due praise by inhabiting its beautiful intellectual architecture. Among the core features observed are Scholasticism’s methodological vitality explained as an exegetical-humility with patristic roots, the animating principle of desire for union with God, and a conception of Christian doctrine as fundamental to the divine work of human salvation. Rather than engage directly with Scholasticism’s fashionable modern enemies, the essay proceeds in successive steps as a lectio magistrorum (“reading of the masters”). Anslem of Canterbury, Hugh of St. Victor, Peter Abelard, Bonaventure, and Thomas Aquinas represent the primary sources of interest. The goal is simply to generate reconsideration of medieval theology through an introduction to atypically studied aspects of a few figures.